Antisolvent Choice Determines the Domain Distribution of Quasi‐2D Perovskite for Blue‐Emitting Perovskites‐Based Light Emitting Devices. Issue 4 (12th December 2022) - Yantara, Natalia; Kanwat, Anil; Furuhashi, Tomoki; Chua, Huei Min; Sum, Tze Chien; Mathews, Nripan
Abstract: Antisolvent treatment is paramount in the fabrication of high‐efficiency perovskite optoelectronic devices as it affords a high crystallization rate critical for the formation of pin holes‐free perovskite films. Although the antisolvent choice determines the domain distribution of quasi‐2D perovskite, and hence the emission wavelength (blue vs green), as well as its light emission efficiency, few studies have examined it in detail. Herein, the crystallization dynamics and resulting optoelectronic properties of PBA (phenyl‐butyl‐ammonium)‐based quasi‐2D perovskites (A′2 A m ‐1 Pb m X3 m +1 ), which are commonly employed to create blue emissive films, are scrutinized for the first time through in situ photoluminescence measurements during film formation. The m domain distribution can be tailored by selecting antisolvents with various solubilities of PBA cation. Antisolvents with higher PBA solubility promote the formation of smaller bandgap films due to larger m domains and vice versa. This study effectively reveals a route to tailor quasi‐2D perovskite optoelectronic properties via antisolvent engineering. Fine‐tuning the optoelectronic properties can be done by blending two antisolvents with contrasting PBA cations solubility. By doing so, a blue emissive light emitting diode with emission wavelength ranging from 471 to 509 nm can be fabricated with an external quantum efficiency of 2.9% at 471 nm. Abstract : Electroluminescence devices with emission wavelength range from 471 to 509 nm are fabricated from single quasi‐2D perovskite precursors recipe via antisolvent engineering method. This is made possible by understanding the 2D cations–antisolvent interaction which governs the domain distribution and optoelectronic properties of quasi‐2D perovskite. The relationship between crystallization and carrier dynamics on the final films is examined.